2003
DOI: 10.1136/ip.9.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safe Kids Week 2001: prevention of scald and burn injuries in young children

Abstract: Objective:To evaluate Safe Kids Week 2001—a national public awareness campaign on scald and burn prevention—run by Safe Kids Canada.Design:Random digit dial telephone survey.Setting:Canada.Subjects:Parents or guardians of children under 9 years. Two groups of parents were compared, those “exposed” to the campaign (defined as having “seen, heard, or read anything about scald and burn prevention during the period 28 May to 3 June 2001”) and those “unexposed” to the campaign.Intervention:Burn safety information w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 11 publications
1
33
0
3
Order By: Relevance
“…Para as que sofrem queimaduras graves, a reabilitação é demorada, há risco de prejuízo do crescimento ósseo e perdas funcionais 55 . A família é atingida, em função do sofrimento da criança e dos gastos financeiros 42 A queimadura é um tipo de injúria que ocorre predominantemente em casa, em especial na cozinha [41][42][43] , acometendo principalmente pacientes de 1 a 4 anos 41 .…”
Section: Queimadurasunclassified
“…Para as que sofrem queimaduras graves, a reabilitação é demorada, há risco de prejuízo do crescimento ósseo e perdas funcionais 55 . A família é atingida, em função do sofrimento da criança e dos gastos financeiros 42 A queimadura é um tipo de injúria que ocorre predominantemente em casa, em especial na cozinha [41][42][43] , acometendo principalmente pacientes de 1 a 4 anos 41 .…”
Section: Queimadurasunclassified
“…42 Those with severe burns have a slow recovery and may have abnormal bone growth and functional loss. 55 Families are affected by their childrens suffering and burdened with financial costs. 42 Hall et al interviewed parents of hospitalized burn victims and found out that three months after the event a significant share (47%) of the children had remarkable symptoms of posttraumatic stress.…”
Section: Burnsmentioning
confidence: 99%
“…[35][36][37] Maintaining tap water at 120°F is a successful strategy for reducing scalds. 7,[38][39][40] Water temperature can be lowered by adjusting the thermostat on the water heater or by an antiscald device at the tap. 1,9,10,12,41 Although not as well documented in terms of efficacy, other safety recommendations include keeping a fire extinguisher in the kitchen for small fires, 7,23 and having a fire escape plan for the household.…”
Section: Introductionmentioning
confidence: 99%